Selective screening for inborn errors of metabolism: past, present and future - Hoffmann, Georg F. (European journal of pediatrics, 1994)
Selective screening for hereditary metabolic disorders has developed from a highly specialized activity, provided mostly by research oriented scientists, to an important diagnostic tool in the work-up of paediatric patients. A brief overview is given of the present status of selective screening in Europe, the USA and Israel including the distribution of centres and resources for diagnosis, therapy and follow-up. Current status and most pressing problems vary widely between different countries. Most countries still lack an organized network of clinical genetic centres which are capable of competent and comprehensive diagnostic and therapeutic services. For example, it must be assumed that more than 60% of patients with inherited metabolic diseases, which could be diagnosed nowadays, remain un(mis)diagnosed in former Western Germany. Early diagnosis and treatment are important determinants for a successful approach towards inherited metabolic diseases. Therefore, screening and therapy for inborn errors of metabolism has to be organized in clinical genetic centres, each serving a population between 2 and 4 million. The quality of the services provided depends on good pre-and postgraduate training of physicians (paediatricians) in the field of metabolic diseases, good co-operation between the referring physician and the clinical genetic centre and a broad spectrum of highly specialized metabolic investigations in the respective centre. The institutionalization has to include licensing of laboratories, directors and personnel, as well as quality control and proficiency testing. The size of the centres cannot be judged on the basis of the work involved with selective screening for inborn errors of metabolism alone. The number of diagnosed patients suffering from treatable metabolic disorders, such as those of amino or organic acid metabolism, are cumulative. The patients need lifelong dietary therapy, clinical assessment and biochemical monitoring.